FDZ data description: The German Heating and Housing Panel (GHHP) - Wave 1 - Manuel Frondel; Andreas Gerster; Kathrin Kaestner; Marielena Krieg; Michael Pahle; Antonia Schwarz; Puja Singhal; Stephan Sommer (RWI - Leibniz-Institut für Wirtschaftsforschung, 2023)
Numerous measures have been taken in recent years to achieve climate protection targets in the building sector. With the newly established Ariadne German Heating and Housing Panel (GHHP), the prerequisite for a well-founded evaluation of the effectiveness, distribution effects and acceptance of climate policy measures in the heating sector has been created for the first time. The GHHP is an annual series of surveys on the heating transition with around 15,000 participating households in Germany. The survey, carried out as part of the Kopernikus project Ariadne funded by the Federal Ministry of Education and Research (BMBF), is made up of around 65% owner-occupied households and 35% renters. In addition to detailed information on the building stock, existing heating systems and heating costs as well as the socio-economic characteristics of the households, the survey also examines energy modernization measures that have already been carried out or are planned. The survey also records households' perception and acceptance of policy instruments in the building sector that are being discussed and have already been introduced. The first survey took place in 2021 and the surveys are to be continued until 2026. This data description provides a brief overview of the first wave of the GHHP in 2021. It explains the process and methodology of data collection as well as the socio-economic characteristics of the sample. Information on how to access the data can be found in section 5; a codebook is included in the appendix. – – Zur Erreichung der Klimaschutzziele im Gebäudesektor wurden in den vergangenen Jahren zahlreiche Maßnahmen ergriffen. Mit dem neu etablierten Ariadne Wärme- und Wohnen-Panel (German Heating and Housing Panel, GHHP) ist erstmals die Voraussetzung für eine fundierte Evaluierung der Effektivität, der Verteilungswirkungen und der Akzeptanz klimapolitischer Maßnahmen im Wärmesektor geschaffen worden. Das Wärme- und Wohnen-Panel ist eine sich jährlich wiederholende Erhebungsreihe zum Thema Wärmewende mit rund 15.000 teilnehmenden Haushalten in Deutschland. Die im Zuge des vom Bundesministerium für Bildung und Forschung (BMBF) geförderten Kopernikus-Projekts Ariadne durchgeführte Erhebung setzt sich aus ca. 65 % Eigentumshaushalten und 35 % Mietenden zusammen. Neben detaillierten Informationen zum Gebäudebestand, bestehenden Heizsystemen und Heizkosten sowie sozioökonomischen Charakteristika der Haushalte untersucht die Erhebung auch bereits durchgeführte oder geplante energetische Modernisierungsmaßnahmen. Darüber hinaus erfasst die Erhebung die Wahrnehmung und Akzeptanz der Haushalte zu diskutierten sowie bereits eingeführten Politikinstrumenten im Gebäudesektor. Die erste Erhebung fand 2021 statt und die Erhebungen sollen bis 2026 fortgeführt werden. Diese Datenbeschreibung gibt einen kurzen Überblick über die erste Welle des Ariadne Wärme- und Wohnen-Panel im Jahr 2021. Sie erläutert den Prozess und die Methodik der Datenerhebung sowie die sozioökonomischen Merkmale der Stichprobe. Informationen über den Zugang zu den Daten sind in Abschnitt 5 zu finden; ein Codebuch ist im Anhang enthalten.
Keywords: 330